EL LUGAR DE LAS ESTRATEGIAS METODOLÓGICAS PARA LA INNOVACIÓN EN LA ENSEÑANZA DE LA GEOGRAFÍA - María N. Prieto; María A. Lorda (Boletín Geográfico)
There is a consensus in the didactic literature about the predominance of the transmissive model in the teaching of geography and, therefore, the construction of a "school geography" based on the "informative" speech. This, although it is important, is based on the exercise of the description as a fundamental communication skill, therefore not prioritizes the development of more complex skills (explanation, interpretation, argumentation and justification) necessary for the understanding of geographical problems. This trend strongly rooted, corresponds to the predominance of traditional or transmissive learning strategies in the classroom of geography, which tend to develop in the student learning strategies based on memorization and repetition. Guide transmissive teaching of geography education explanatory and interpretative from active teaching strategies requires a critical and reflective stance of teaching that encourages the adoption of content based from the new epistemological positions and with active methodological treatments on the basis of the consideration of the importance of developing in students the meaning of the geography for your everyday life and critical thinking for the formation of critical citizenscommitted and thoughtful.